OP0076 Dysregulated Bioenergetics within the Inflamed Joint. (9th June 2015) - Biniecka, M.; Canavan, M.; Ng, V.; Smith, T.; McGarry, T.; Veale, D.; Fearon, U.
Abstract : Background: Hypoxia is a powerful trigger of synovial fibroblast and endothelial cell activation, proliferation and survival. Metabolic turnover of the inflamed synovium outpaces a dysfunctional vascular supply. This may induce a cellular switch in energy production characterized by an increase in glycolytic flux and suppression of mitochondrial functions, an effect that can regulate abnormal angiogenesis, immune responses and cellular invasion. Objectives: To examine the relationship between synovial hypoxia, cellular bioenergetics and mitochondrial dysfunction with synovial inflammation. Methods: Primary RASFC were cultured with 1% hypoxia, DMOG (stabilizes HIF1a) or lactic acid. Reactive oxygen species (ROS), mitochondrial membrane potential (MMP) and mitochondrial mass (MM) were quantified using fluorescent probes, RASFC invasion by Transwell Matrigel™ chambers, and VEGF, bFGF by ELISA. Alterations in the synovial mitochondrial genome were assessed by Random Mutation Capture assay. RASFC metabolism was assessed by the XF24 Flux analyser (Seahorse) which simultaneously quantifies real-time measurements of aerobic (Oxygen Consumption Rate) and anaerobic (Extracellular Acidification) bioenergetic profiles. To examine if altered metabolism is also observed in vivo, 44 patients with active inflammatory arthritis underwent arthroscopy, clinical assessment and synovial tissue oxygen (tpO2 ) measurements. Synovial microscopic levels of glycolysis and oxidative phosphorylation (GAPDH, PKM2, GLUT1, ATP), inflammation (CD3, CD68) and angiogenesis (FactorVIII/aSMA) were quantified by immunohistology. A subgroup of patients underwent contiguous MRI and PET/CT imaging. Results: In RASFC, hypoxia induced increased mitochondrial DNA mutations, MM, MMP, ROS and invasion but inhibited ATP indicating altered cellular energy metabolism (all p<0.01). Hypoxia increased the rate of glycolysis with concomitant attenuation of mitochondrial respiration (p<0.01), decreased basal and maximal respiration (p<0.01) with a simultaneous induction in glycolytic cell activity (p<0.001). Hypoxia inhibited RASFC glucose secretion (p<0.05) and increased lactate levels (p<0.05). Lactic acid in turn, induced RASFC invasion and secretion of bFGF and VEGF. Elevated RASFC glycolysis was concurrent with in vivo assessments, with synovial expression of GAPDH, PKM2 and GLUT1 significantly higher in patients with tpO2 levels in vivo <20mmHg (all p<0.05), in contrast to ATP which was significantly lower (p<0.05). Glycolytic marker expression also correlated with increased macroscopic/microscopic vascularity and synovitis (all p<0.05). Finally, PET/MRI hybrid images demonstrated close association between metabolic turnover and site of inflammation with tpO2 levels in vivo . Conclusions: Hypoxia alters cellular bioenergetics by down-regulating mitochondrial respiration and promoting a switch to glycolysis in the inflamed joint. This may enable synovial cells to generate sufficient ATP to support enhanced synovial proliferation, angiogenesis and pannus formation. Disclosure of Interest: M. Biniecka: None declared, M. Canavan: None declared, V. Ng: None declared, T. Smith: None declared, T. McGarry: None declared, D. Veale Grant/research support from: Abbvie, MSD, Pfizer, Roche, Consultant for: Pfizer, Roche, Speakers bureau: Abbott, MSD, Pfizer, Roche, U. Fearon: None declared